Homocysteine metabolism in rats with metabolic syndrome and the impacts of nigella sativa oil on some biochemical parameters - Alayunt, Naci Ömer; Üstündağ, Bilal (My University, 2020)
The high level of fructose taken in the diet is one of the reasons for the increased prevalence of metabolic syndrome,which is increasing day by day globally in association with the effects of genetic and environmental factors. In thestudy, 21 male Sprague-Dawley rats of 220±20 gr body weight were used. The rats were assigned to 3 groups as thecontrol group, metabolic syndrome group, and the group where Nigella sativa oil was administered. The serum homocysteine levels were increased in the metabolic syndrome group compared to the control group but without statisticalsignificance (p>0.05). Homocysteine levels decreased significantly after Nigella sativa oil compared to metabolicsyndrome group. LDH (p <0.001) and uric acid (p <0.05) levels which were higher in metabolic syndrome groupwere decreased in Nigella sativa oil group. Hyperhomocysteinemia is a risk factor for endothelial dysfunction. In ourstudy, the treatment of the metabolic syndrome and regulation of the increased levels of homocysteine with Nigellasativa oil in metabolic syndrome were discussed. Some biochemical parameters and improvements in homocysteinelevels with Nigella sativa oil has been identified. In this study, we have concluded that the occurrence of elevated levels of plasma homocysteine are closely associated with the development of inflammation, cellular adhesion, hepaticdysfunction, and cell proliferation and that the reduction in the serum levels of homocysteine by the administrationof Nigella sativa oil will lead to favorable out comes.
Keywords: Tıbbi Araştırmalar Deneysel; Endokrinoloji ve Metabolizma; Genel ve Dahili Tıp